Hubungan Pendidikan Dan Kehamilan Usia Dini Dengan Kejadian Kekurangan Energi Kronik Pada Ibu Hamil Di Wilayah Kerja Puskesmas Karya Sakti Musi Rawas - Annisa, Kintan; Umami, Desi Aulia; Sulistiwati, Niken (Universitas Dehasen Bengkulu, 2025)
Chronic Energy Deficiency (KEK) is a condition of nutritional deficiency in pregnant women. The problem in this research is the increase in the incidence of KEK in the West Lingkar Community Health Center by 10.02% from 2016 of 3.68% and in 2017 of 14.7%. This study aims to determine the relationship that influences CED in pregnant women at the Karya Sakti Musi Rawas health center. The type of research in this research is an analytical survey with a Case Control approach. The sample in this study consisted of 44 pregnant women. The research was conducted using univariate and bivariate analysis. The results showed that education (p=0.016) and early age of pregnancy (p=0.033) were related to the incidence of CED. It is hoped that the Community Health Center can improve the treatment program for CED pregnant women and carry out early detection of factors that cause CED in pregnant women.